Increase in requests for D-dimer in the first wave of COVID-19 in a university hospital in the metropolitan region of the State of Rio de Janeiro (Research, Society and Development, 2021)
Introduction: D-dimer is a fibrin degradation product and is an indirect marker of fibrinolysis. If an individual infected with SARS-COV 2 evolves with aggravation, a result equal to or greater than four times the reference value of this marker at the time of admission is considered a predictor of mortality. The most important exam since the beginning of the pandemic, due to the thrombotic manifestations resulting from the infection. Objective: To evaluate the variation in the number of medical requests for D-dimer dosage at a given University Hospital and its profile in the first wave of the COVID-19 pandemic. Methodology: This is a cross-sectional observational study, where the results of patients with a COVID-19 profile, identified in the Emergency Laboratory of a University Hospital, were quantified and medical causes for D-dimer dosages in the period from 03/01/2020 to 07/03/2020. Results: In the first half of 2020, we observed 1017 requests. Comparing the 1st quarter with the 2nd quarter of the same year, there was an abrupt increase of 1274%, no total occurrences from one quarter to the other, since no 1st quarter, only 69 requests were detected with a median 2231 ng / mL ( interquartile range 175-15605), no longer 2nd quarter this number jumped to a total of 948 requests with a median 2020 ng / mL (interquartile range 99-97026). Conclusion: Although D-dimer does not have high specificity as a diagnostic tool, it has been very useful as a severity predictor for COVID 19. Despite the enormous impact generated by the substantial increase in demand for D-dimer demand in this University Hospital, have provoked a solution of continuity in the provision of services, further studies in risk and disaster management would be opportune, in order to improve the resolving flow for situations that, unfortunately, may occur.